Monotone empirical bayes test for the parameter of pareto distribution under random censorship. Issue 4 (3rd July 2016) - He, Bang-Qiang; Ni, Wenqing; Zhou, Jin-Ming
Abstract: This article considers the monotone empirical Bayes (MEB) test problem for the parameter of Pareto distribution with censored data. We construct the MEB test rule for the parameter of Pareto distribution under random censorship. It is shown that the proposed MEB test have asymptotically optimal property. The convergence rate of the MEB test is obtained and the rate can approach to O ( n – ½) arbitrarily under suitable conditions.